Lithium and suicide prevention in mood disorders and in the general population: A systematic review. (September 2020) - Del Matto, L.; Muscas, M.; Murru, A.; Verdolini, N.; Anmella, G.; Fico, G.; Corponi, F.; Carvalho, A.F.; Samalin, L.; Carpiniello, B.; Fagiolini, A.; Vieta, E.; et al.
Highlights: Most ecological studies about lithium in drinking water report a reduction in suicide in general population, mostly in males. Most trials, uncontrolled and controlled open label, show a reduction in the risk of suicide under long-term lithium use. Evidence seems to attribute an intrinsic anti-suicidal property of lithium, independent of its efficacy as mood stabilizer. Abstract: Suicide contributes to 1–4 % of deaths worldwide every year. We conducted a systematic review aimed at summarizing evidence on the use of lithium for the prevention of suicide risk both in mood disorders and in the general population. We followed the PRISMA methodology (keywords: "lithium", "suicide" AND "suicidal" on Pubmed, Cochrane CENTRAL, Clinicaltrial.gov, other databases). Inclusion criteria: lithium therapy in mood disorder or found in drinking water or scalp in the general population. Exclusion criteria: no lithium administration. From 918 screened references, 18 prospective (number of participants: 153786), 10 retrospective (number of participants: 61088) and 16 ecological studies (total sample: 2062) were included. Most of the observational studies reported a reduction in suicide in patients with mood disorders. All studies about lithium treatment's duration reported that long-term lithium give more benefits than short-term lithium in suicide risk The evidence seems to attribute an intrinsic anti-suicidal property of lithium, independent of its proven efficacy as a mood stabilizer.